2009
DOI: 10.1111/j.1467-7652.2009.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel real‐time polymerase chain reaction method for high throughput quantification of small regulatory RNAs

Abstract: SummaryMicroRNAs (miRNAs) and small interfering RNAs (siRNAs) are important players of both transcriptional and post-transcriptional gene silencing networks. In order to investigate the functions of these small regulatory RNAs, a system with high sensitivity and specificity is desperately needed to quantitatively detect their expression levels in cells and tissues.However, their short length of 19-24 nucleotides and strong similarity between related species render most conventional expression analysis methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…Besides the relative quantification of miRNA expression, the synthetic miRNA standards could also allow the absolute quantification of miRNA expression from total RNA samples. In contrast to the previously reported miRNA real-time PCR assays that were performed under standard thermocycling profiles of 45-75 sec per cycle (Chen et al 2005;Raymond et al 2005;Shi and Chiang 2005;SharbatiTehrani et al 2008;Yang et al 2009), our assay was capable of fast thermocycling (10 sec per cycle) without any modification of the reaction mixtures. The fast-cycling capability of this assay may, in part, be attributed to the short amplicon (<50 base pairs) generated by heminested primers and the rapid fluorescence acquisition of SYBR Green I without the necessity of probe hydrolysis.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Besides the relative quantification of miRNA expression, the synthetic miRNA standards could also allow the absolute quantification of miRNA expression from total RNA samples. In contrast to the previously reported miRNA real-time PCR assays that were performed under standard thermocycling profiles of 45-75 sec per cycle (Chen et al 2005;Raymond et al 2005;Shi and Chiang 2005;SharbatiTehrani et al 2008;Yang et al 2009), our assay was capable of fast thermocycling (10 sec per cycle) without any modification of the reaction mixtures. The fast-cycling capability of this assay may, in part, be attributed to the short amplicon (<50 base pairs) generated by heminested primers and the rapid fluorescence acquisition of SYBR Green I without the necessity of probe hydrolysis.…”
Section: Discussionmentioning
confidence: 86%
“…1). Initially, we noticed that in a number of previous reports (Chen et al 2005;Raymond et al 2005;Shi and Chiang 2005;Duncan et al 2006;Varkonyi-Gasic et al 2007;Sharbati-Tehrani et al 2008;Yang et al 2009), the reverse PCR primers were designed to anneal directly to the sequences in the RT oligonucleotide. To achieve specificity, a unique miRNA-specific fluorescent probe is required to discriminate the targets from the nonspecific amplicons (Chen et al 2005).…”
Section: Overview Of a Hemi-nested Real-time Rt-pcr Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods, such as northern blot [36], beadbased flow cytometry, [37] microarray, quantitative realtime PCR (qRT-PCR) [38], and deep sequencing [39] have been developed to measure miRNA expression. Of these methods, Mestdagh P et al [40] reported that qRT-PCR is superior due to its high sensitivity, specificity and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is more sensitive, easier, and less time-consuming than approaches such as cloning, northern blotting, microarray analysis, and deep sequencing, a combination of reverse transcription (RT) and quantitative PCR, or RT-qPCR, is currently the most convenient and practical means of detecting precursor and mature miRNAs. Four well-developed RT-qPCR methods of miRNA detection, each with its own advantages and disadvantages, have recently become established: stem-loop RT-qPCR, 2) poly(A)-tailing RT-PCR, 3) primer-extension RT-qPCR 4) with various improvements, [5][6][7][8][9] and miQPCR. 10) Although stem-loop RT-qPCR is the most frequently used of these methods, in previous studies we were unable to detect certain rice miRNAs using it.…”
mentioning
confidence: 99%